Enriched bovine IgG fraction prevents infections with Enterohaemorrhagic Escherichia coli O157:H7, Salmonella enterica serovar Enteritidis, and Mycobacterium avium - Keiji Funatogawa (Food Science & Nutrition, 2019)
Abstract A bovine IgG‐enriched whey fraction contains antibodies against various bacterial antigens. We investigated the protective effects of a bovine whey fraction preparation against infections with Enterohaemorrhagic Escherichia coli O157:H7, Salmonella enterica serovar Enteritidis, and Mycobacterium avium in mouse models. After infection with these pathogens, the IgG‐enriched fraction or skim milk was given ad libitum at a 5% solution instead of water. The mice given the IgG‐enriched fraction were significantly resistant to orally challenged EHEC O157:H7 (LD50: 4.0 × 105 CFU/mouse) infections compared with the mice given skim milk (LD50: <1.5 × 102 CFU/mouse). The mice given the IgG‐enriched fraction were also significantly resistant to orally challenged S. Enteritidis (LD50: 5.0 × 106 CFU/mouse) infections compared with the mice given skim milk (LD50: <2.5 × 101 CFU/mouse). When the mice were nasally infected with M. avium, the numbers of the bacteria in lungs of mice given the IgG‐enriched fraction were significantly lower than those given skim milk 2 and 3 weeks after infection. These results strongly indicate that oral administration of the bovine IgG‐enriched whey fraction protects mice against food‐borne infection and also that it partially protects mice against respiratory tract infection.